Dental Erosion and Its Clinical Management 2015
DOI: 10.1007/978-3-319-13993-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Dental Erosion: Intrinsic Factors

Abstract: The consequences of the severe wear caused by intrinsic erosion, in addition to the high cost and complexity of the treatment to restore severely worn dentition, support the importance of early diagnosis and implementation of preventive/therapeutic measures. Dental professionals must be aware of the signs and symptoms of the disease, as well as all the conditions that may lead to the presence of gastric juice in the mouth, so they can make the referral to the appropriate medical specialist. In this chapter, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 148 publications
(82 reference statements)
0
16
0
2
Order By: Relevance
“…68 Exposed to food, drink, and the microbiota of the mouth, teeth have developed a high resistance to localized demineralization unmatched by other mineralized tissues. 59,69 This resistance is chiefly due to the enamel layer that covers the crown of the teeth. 70,71 Chemical demineralization of teeth is caused by acidic attack through two primary means: dietary acid consumed through food or drink and microbial attack from bacteria present in the mouth.…”
Section: Demineralizationmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Exposed to food, drink, and the microbiota of the mouth, teeth have developed a high resistance to localized demineralization unmatched by other mineralized tissues. 59,69 This resistance is chiefly due to the enamel layer that covers the crown of the teeth. 70,71 Chemical demineralization of teeth is caused by acidic attack through two primary means: dietary acid consumed through food or drink and microbial attack from bacteria present in the mouth.…”
Section: Demineralizationmentioning
confidence: 99%
“…70,71 Chemical demineralization of teeth is caused by acidic attack through two primary means: dietary acid consumed through food or drink and microbial attack from bacteria present in the mouth. 69,72,73 Published literature in this area seeks to apply chemical theory to the erosion of dental hard tissues, chiefly enamel. 59,74,75 During an acidic attack, or a typical demineralization regime, chemical dissolution of both the organic and inorganic matrix components takes place.…”
Section: Demineralizationmentioning
confidence: 99%
“…While tooth brush users showing only an increase in salivary calcium, a significant rise was observed in both salivary Ca and plaque Na and calcium, following a sucrose meal among Miswak users. This feature was unique for Miswakusers, since most recent studies have shown a decrease in concentrations of Ca, P and fluoride ions, in the presence of sucrose, so leading to plaque biofilm formation [21][22][23]. While demineralization is the process of removing minerals ions from the stoichiometric hydroxyapatite crystals of hard tissues (enamel, dentin, cementum, bone), remineralization is a reverse process of restoring these ions.…”
Section: Discussionmentioning
confidence: 99%
“…While demineralization is the process of removing minerals ions from the stoichiometric hydroxyapatite crystals of hard tissues (enamel, dentin, cementum, bone), remineralization is a reverse process of restoring these ions. Teeth demineralization results from the acidic effect by two ways: Acid notably content of sugary foods and drinks, and microbial attack from oral bacteria [21][22][23]. The balance between demineralization and remineralization is kept through calcium, phosphate, and fluoride, and also regulated by salivary pH, which plays an important role in modifying the susceptibility of tooth to caries progression [24].…”
Section: Discussionmentioning
confidence: 99%
“…3 [ 38 ] of this book, one of the factors that can predispose individuals to the risk of dental erosion is their lifestyle. The conventional oral health education approach focuses on offering information and advice, which improve the patient's knowledge but may not translate into sustained changes in behaviour.…”
Section: Oral Health Education To Prevent and Control Erosionmentioning
confidence: 99%